Essays on the Political Economy of Institutions - (:unkn) unknown (My University, 2014)
There is a consensus among economists and political scientists that institutions are crucial for economic development. Different attributes of institutions like rule of law, property rights, legal environment, and constraints on executive have profound effects on a nation's prosperity, growth and development. Recently economists have recognized that a system of strong institutions of property rights can enhance efficiency of financial sector. A significant part of the dissertation deals with the question that is it likely that causality operates the other way: Does a mature financial market acts as a strong catalyst for property rights? The first essay develops a theoretical model of financial intermediation with incomplete information to augment the notion. The model predicts that the relationship does exist and is in fact nonlinear. Thus finance acts as propellant for property rights only after crossing a certain threshold. The second essay presents empirical evidence of threshold effects in the cross country relationship between property rights and finance that are consistent with the theory. Further, in a panel of countries, I show that the exogenous component of financial development helps predict property rights in a sample of countries where financial markets have crossed a threshold level of development. The final essay of the dissertation deals with the effects of legal environment on financial market. More specifically, it explores the effects of collateral law reforms on firms' perceived access to finance by taking a panel of developing countries. I find evidence that collateral law reforms are effective in improving perceived access to credit. Moreover the effects are more pronounced when they are accompanied by established collateral registries for movable and intangible assets. Finally these beneficial effects seem to increase in the size of the firms.